The comparative efficacy of yohimbine and atipamezole to treat amitraz intoxication in dogs - Andrade, Silvia Franco; Sakate, Michiko [UNESP] (My University, 2003)
This study compared the efficacy of yohimbine with atipamezole, a new α2-adrenergic antagonist, to treat canine amitraz intoxication. Thirty dogs were divided equally into 3 groups (A, AY, and AA). Group A received 2.5% amitraz iv at 1 mg/kg; Group AY received the same dose of amitraz followed 30 min later by 0.1 mg/kg (2 mg/mL) yohimbine iv; and Group AA received the same dose of amitraz followed 30 min later by 0.2 mg/kg (5 mg/mL) atipamezole iv. Temperature, heart rate, respiratory frequency, mean arterial pressure, degree of sedation, mean time of tranquilization and diameter of pupils were monitored for 360 min. Sedation, logs of reflexes, hypothermia bradycardia, hypotension, bradypnea and mydriasis were observed in Group A, with 3rd eyelid prolapse, increased diuresis and vomiting in some animals. Yohimbine reversed all alterations induced by amitraz, but induced significant cardiorespiratory effects such as tachycardia and tachypnea. Atipamezole was a useful antagonist for amitraz, with less cardiorespiratory effects, suggesting its potential role as an alternative treatment of amitraz intoxication in dogs.
Keywords: amitraz; atipamezole; yohimbine; animal experiment; animal model; controlled study; dog; drug efficacy; drug intoxication; ectoparasite; ingestion; intestine motility; mean arterial pressure; nonhuman; respiration depression; thermoregulation; Adrenergic alpha-Antagonists; Animals; Dog Diseases; Dogs; Female; Imidazoles; Infusions, Intravenous; Male; Poisoning; Toluidines; Treatment Outcome; Yohimbine; Animalia; Canis familiaris